E0289 Association of low ankle-brachial index with mortality in patients with ischaemic heart disease. (17th November 2010) - Liqiang, Zheng; Jue, Li; Dayi, Hu; Yingyi, Luo; Xiankai, Li; Yuanxi, Xu
Abstract : Objective: To find out whether a low ankle-brachial index can improve the prediction of and cardiovascular mortality on top of conventional risk factors remains unclear among patients with ischaemic heart disease. The present study was to assess the association between ankle-brachial index and mortality in Chinese patients. Methods: An observational prospective study was conducted in which 1, 800 Chinese patients aged ≥35 years were followed-up from 2004 to 2007–2008. Results: There were 280 deaths, of which 165 were attributable to cardiovascular disease. Compared with patients with an ankle-brachial index ≥1.1, the risk of mortality increased linearly in lower ankle-brachial index categories: patients with an ankle-brachial index of 0.9 to 1.1, 0.7 to 0.9, <0.7 had HR of 1.60, 2.07, 3.08 for mortality and 1.89, 2.33, 4.09 for cardiovascular mortality (p for trend<0.001) respectively. Addition of ankle-brachial index significantly (p<0.001) increased the predictive value of the model for 3-year deaths compared with a model containing risk factors alone. Comparison of areas under receiver operator characteristics curves confirmed that a model including the ankle-brachial index discriminated better than one without. Conclusions: There was an inverse association between ankle-brachial index and mortality. Addition of ankle-brachial index significantly improved the prediction of 3-year mortality over and above that of conventional risk factors. We recommend that ankle-brachial index be incorporated into prognostic assessment for patients with ischaemic heart disease.